2011
DOI: 10.1093/ilar.52.3.239
|View full text |Cite
|
Sign up to set email alerts
|

Translational Models of Interactions Between Stress and Alcohol Consumption: Strengths and Limitations

Abstract: Much has been written about the interaction of stressors (physical, social, and psychological) and alcohol addiction based on studies in humans and preclinical models. We begin by considering the significance and complexity of alcoholism and the options for effectively modeling it in animals, particularly rodents. We then focus on the following aspects of stress-alcohol interactions: (1) compulsive alcohol consumption, characterized by continued intake despite the presence of stressful or aversive consequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 156 publications
0
15
0
Order By: Relevance
“…Clinical evidence supports a life history of adverse events as an antecedent for problematic drinking (e.g., Annis et al 1998; Blanco et al 2013; Brown et al 2012; Dawson et al 2005; Heilig et al 2010; Nishith et al, 2001; Noone et al 1999; Sinha et al 2009; Uhart and Wand 2009) and stress-alcohol cross-sensitization has been theorized, in part, to contribute to this relation (c.f., Burke and Miczek 2014; Hopf et al 2011). It has long been recognized that the ability to predict a stressor is a major factor determining an individual’s biobehavioral response to the stressor (c.f., Koolhaus et al 2005) and that chronic exposure to unpredictable stressors produces a robust, depressive-like, phenotype in laboratory rodents that is associated with perturbations within the biochemistry of neural circuits subserving motivation (c.f., Willner, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence supports a life history of adverse events as an antecedent for problematic drinking (e.g., Annis et al 1998; Blanco et al 2013; Brown et al 2012; Dawson et al 2005; Heilig et al 2010; Nishith et al, 2001; Noone et al 1999; Sinha et al 2009; Uhart and Wand 2009) and stress-alcohol cross-sensitization has been theorized, in part, to contribute to this relation (c.f., Burke and Miczek 2014; Hopf et al 2011). It has long been recognized that the ability to predict a stressor is a major factor determining an individual’s biobehavioral response to the stressor (c.f., Koolhaus et al 2005) and that chronic exposure to unpredictable stressors produces a robust, depressive-like, phenotype in laboratory rodents that is associated with perturbations within the biochemistry of neural circuits subserving motivation (c.f., Willner, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Peptide systems such as cotricotrophin releasing factor (CRF) and neuropeptide Y (NPY) have also received attention because of their recognized role in anxiety and their activity in the extended amygdala. More recent research has recognized that stress-associated systems play a key role in the development and maintenance of AUD and addiction in which withdrawal plays an important part (See Griffin, 2014; Hopf et al, 2011). Therefore, stress-associated seeking and/or craving behavior has received research interest but mostly in non-selectively bred (i.e., outbred) rat lines.…”
Section: Behavioral Models For Screening Treatment Compounds And/omentioning
confidence: 99%
“…One critical parameter is that it is difficult to fine-tune the foot-shock parameters, for example applied mA and duration of shock. Thus, investigators attempting to study footshock-induced reinstatement of alcohol seeking have found this to be a quite variable phenomenon, and in fact, the relationship between different stressors and alcohol seeking is mixed and complex (Hopf, Sparta, & Bonci, 2011). It is also difficult to know what each rat is experiencing during the footshock and how much this varies between animals.…”
Section: Quinine Versus Footshock As An Aversive Consequence Paired Wmentioning
confidence: 99%